Analysis of the impact of implementing digital marketing tools in micro and small businesses (Research, Society and Development, 2024)
Digital Transformation can be defined as a new way for companies to think, supported by the use of technologies. The Local Innovation Agents (ALI) Digital Transformation program seeks to promote this philosophy among micro and small businesses throughout the country. Several companies are monitored through a methodology that has varied activities, including the hiring of technology. Among the different types of technology are Digital Marketing tools, which emerge as an interesting alternative in the current days of need for an online presence. The goal of this study is to perform a quantitative analysis of the data collected in this cycle with a view to the use of digital marketing tools in small businesses. Both the quantitative numbers of the program and the perception of ALI regarding the use of digital marketing tools in small businesses were analyzed. The data analysis highlights the impacts of the use of digital marketing in these companies, pointing out directions to enhance actions in favor of a digital transformation of micro and small entrepreneurs.